Glucose impairs B‐1 cell function in diabetes. (8th September 2013) - Jennbacken, K.; Ståhlman, S.; Grahnemo, L.; Wiklund, O.; Fogelstrand, L.
Summary: B‐1 lymphocytes produce natural immunoglobulin (Ig)M, among which a large proportion is directed against apoptotic cells and altered self‐antigens, such as modified low‐density lipoprotein (LDL). Thereby, natural IgM maintains homeostasis in the body and is also protective against atherosclerosis. Diabetic patients have an increased risk of developing certain infections as well as atherosclerosis compared with healthy subjects, but the underlying reason is not known. The aim of this study was to investigate whether diabetes and insulin resistance affects B‐1 lymphocytes and their production of natural IgM. We found that diabetic db/db mice had lower levels of peritoneal B‐1a cells in the steady state‐condition compared to controls. Also, activation of B‐1 cells with the Toll‐like receptor (TLR)‐4 agonist Kdo2‐Lipid A or immunization against Streptococcus pneumoniae led to a blunted IgM response in the diabetic db/db mice. In‐vitro experiments with isolated B‐1 cells showed that high concentrations of glucose, but not insulin or leptin, caused a reduced secretion of total IgM and copper‐oxidized (CuOx)‐LDL‐ and malondialdehyde (MDA)‐LDL‐specific IgM from B‐1 cells in addition to a decreased differentiation into antibody‐producing cells, proliferation arrest and increased apoptosis. These results suggest that metabolic regulation of B‐1 cells is of importance for the understanding of the role of this cell type in life‐style‐related conditions.